Collective Modified Value at Risk in Life Insurance - Muhammad Iqbal Al-Banna Ismail; Abdul Talib Bon; Sukono Sukono; Adhitya Ronnie Effendie (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Insurance is seen as a tool which individuals can transfer risks to others, where insurance collect funds from individuals to meet financial needs related to damage. Therefore analysis of risk in life insurance claims is really be needed bt the insurance company actuary. In an insurance system, the risk is the event when an insured party puts forward a claim. Claim is the compensation for a risk loss. Individual claim in one period insurance is called aggregation claim while aggregation claim is collective risk